2002
DOI: 10.2320/matertrans.43.2120
|View full text |Cite
|
Sign up to set email alerts
|

Solubilities and Equilibrium Distribution Coefficients of Oxygen and Carbon in Silicon

Abstract: Solubilities of oxygen and carbon in solid silicon at 1673 K were determined by using a chemical equilibrium technique. Solid silicon was heated at 1673 K in an oxygen atmosphere for 1800 ks, and then oxygen content in the solid silicon equilibrated with silica was measured by the inert gas fusion-IR absorption method. Carbon content in the solid silicon equilibrated with silicon carbide after heating at 1673 K in an Ar-5%CO atmosphere for 4860 ks was measured by the combustion-IR absorption method. Comparing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…Li's experiments [5] showed that the thickness of the continuous SiC layer formed on the glassy carbon surface was B6 mm after 1 h at 1430 C, and they also noted that most of the SiC layer was formed in the first few minutes. Zhou's results [25] also showed that the thickness of the beta-SiC layer [20,22] formed on the glassy carbon surface at 1430 C in 10 min is B4 mm. Although all these analyses show that a B3 mm graphite particle will transform into an SiC particle in minutes, FTIR measurements did not detect the absorption peak due to SiC located at 780-820 cm À1 .…”
Section: Reactions In the Molten Silicon-particles Systemmentioning
confidence: 89%
“…Li's experiments [5] showed that the thickness of the continuous SiC layer formed on the glassy carbon surface was B6 mm after 1 h at 1430 C, and they also noted that most of the SiC layer was formed in the first few minutes. Zhou's results [25] also showed that the thickness of the beta-SiC layer [20,22] formed on the glassy carbon surface at 1430 C in 10 min is B4 mm. Although all these analyses show that a B3 mm graphite particle will transform into an SiC particle in minutes, FTIR measurements did not detect the absorption peak due to SiC located at 780-820 cm À1 .…”
Section: Reactions In the Molten Silicon-particles Systemmentioning
confidence: 89%
“…[11] From Aalberts and Verheijke. [12] # From Narushima et al [13] : presented a range of segregation coefficients for O and C reported by different authors. **From Nozaki et al [14] From Hopkins et al [15] : The segregation coefficients were referred to as effective coefficients, which might be equal to or larger than the actual equilibrium coefficients.…”
Section: B Macrosegregation In Silicon Ingotsmentioning
confidence: 97%
“…Finally, Eq. [13] guarantees that the concentration at the edge of the stagnant layer equals that in the outside mixed liquid, enforcing continuity of the concentration profile throughout the liquid.…”
Section: Mathematical Model Of Macrosegregation For Unidirectionamentioning
confidence: 98%
See 1 more Smart Citation
“…In this calculation, the relative distance from the ingot base was adopted as the solid fraction, the average carbon concentration was assumed as 1200 ppmw, and a solute partition coefficient of 0.034, which is one of the lowest values reported in the literature, [11] was considered. The discrepancy between the measured and calculated profiles is evident.…”
Section: Effects Of Mold Pulling Velocity On Carbon Macrosegregationmentioning
confidence: 99%